2013
DOI: 10.1103/physrevb.88.165301
|View full text |Cite
|
Sign up to set email alerts
|

Nontrivial topological electronic structures in a single Bi(111) bilayer on different substrates: A first-principles study

Abstract: Electronic structures, minimum energy configurations, and band topology of strained Bi(111) single bilayers placed on a variety of semiconducting and insulating substrates are investigated using first-principles calculations. A topological phase diagram of a free-standing Bi bilayer is presented to help guide the selection of suitable substrates. The insulating hexagonal-BN is identified as the best candidate substrate material for supporting nontrivial topological insulating phase of Bi bilayer thin films. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 56 publications
5
108
0
Order By: Relevance
“…The influence of several traditional substrates, e.g. hexagonal boron-nitride (h-BN) and silicon-carbide [165], has been intensively studied. It has been shown that h-BN is an ideal substrate for stabilizing the topologically nontrivial phase of a freestanding Bi bilayer.…”
Section: Bismuth Bilayermentioning
confidence: 99%
“…The influence of several traditional substrates, e.g. hexagonal boron-nitride (h-BN) and silicon-carbide [165], has been intensively studied. It has been shown that h-BN is an ideal substrate for stabilizing the topologically nontrivial phase of a freestanding Bi bilayer.…”
Section: Bismuth Bilayermentioning
confidence: 99%
“…Considering compatibility of lattice constant, we explore strain-driven TI phase transition in DB-SnCH 3 . Figure 3 SiC is an important semiconductor to support 2D materials to realize QSHE, including Bi bilayers [47] . Here, we construct two kinds of HTSs, such as monolayer (ML) SiC and 5-ML SiC layers, to support DB-SnCH 3 .…”
Section: (D) After Structural Optimization the Buckling Heightmentioning
confidence: 99%
“…Beyond carbon [12], the predicted 2D-TIs include films of silicon, germanium [13], tin [14], and bismuth [15], and InBi, GaBi, and TlBi [16] alloys at their equilibrium honeycomb structures, while arsenic [17], antimony [18], BBi, and AlBi [16] transition to a 2D TI phase under strain. Several of the newly predicted 2D-TIs exhibit band gaps large enough to exceed thermal excitation energy at room temperature [15,16,[18][19][20]. Notably, in analogy with graphene, silicene, germanene, and stanene [21], we may refer to a monolayer film of bismuth and antimony of interest to this study as bismuthene and antimonene.…”
Section: Introductionmentioning
confidence: 98%